Karakteristik Petani Ubi Jalar Ungu dan Perkembangan Penerapan Prosesi Kasalasa Sebagai Kearifan Lokal di Kabupaten Muna - Baka, Wa Kuasa; Rianse, Ilma Sarimustaqiyma; Syarni, Pertiwi; Rianse, Usman; Sadimantara, Fahria Nadiryati; Yusran, Yusran (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2019)
Farmers in West Muna Regency firmly believed that the good production of purple sweet potatoes has been related to well-known local wisdom called Kasalasa. The goal of agricultural development is also determined by the quality of human farmers as development actors. The quality of farmers is related to the characteristics of farmers. The objective of the study was to find out the characteristics of purple sweet potato farmers in West Muna Regency and to describe the procession of Kasalasa tradition practiced in West Muna Regency. The study was conducted in Lalemba Village, Lawa Sub-District and Wulanga Jaya Village, Tiworo Sub-District. Locations were selected by the purposive method. Determination of respondents was done by quota sampling, which was 15 people per village, so the number of respondents was 30 people. This research is survey research that uses quantitative and qualitative descriptive analysis. Purple sweet potato farmers in West Muna Regency have an average productive age (45.64 years). The level of education pursued by purple sweet potato farmers is the junior secondary level, which is 66.7 percent. The land is used by farmers for purple sweet potato cultivation is mostly in the range of 0.20 - 0.47 ha, 56.7 percent. The number of family dependents, ranging from 4-6 people or reaching 70 percent. Most purple sweet potato farmers are local of the MunanessEtnic, about 56.7 percent. The orientation of purple sweet potato farmers is still divided into two groups, the first group is commercial orientation, as much 50 percent and the second group is subsistence orientation, as much 50 percent. Kalasa tradition was still practiced by the farmers in West Muna Regency, and such tradition gave motivation and belief to the farmers that the purple sweet potatoes would be free from any kinds of pests and diseases, ghost disruption, and other farmers and human distraction.